2015
DOI: 10.1590/1414-431x20144226
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y, substance P, and human bone morphogenetic protein 2 stimulate human osteoblast osteogenic activity by enhancing gap junction intercellular communication

Abstract: Bone homeostasis seems to be controlled by delicate and subtle “cross talk” between the nervous system and “osteo-neuromediators” that control bone remodeling. The purpose of this study was to evaluate the effect of interactions between neuropeptides and human bone morphogenetic protein 2 (hBMP2) on human osteoblasts. We also investigated the effects of neuropeptides and hBMP2 on gap junction intercellular communication (GJIC). Osteoblasts were treated with neuropeptide Y (NPY), substance P (SP), or hBMP2 at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…At concentrations higher than 10 −5 mM, SP stimulates OB differentiation and bone matrix mineralization, but lower concentrations of SP blocks osteogenic differentiation and induces proliferation of rat bone marrow MSCs and general protein synthesis . Recent studies showed that SP (10 −5 mM) increased ALP and osteocalcin activity in human OB proliferation and mineralization through increased GJIC between OBs . GJIC has important roles in conveying the anabolic effects of hormones and growth factors and regulating transcription of osteogenic markers…”
Section: Peptides From Nervous Systemsupporting
confidence: 86%
See 3 more Smart Citations
“…At concentrations higher than 10 −5 mM, SP stimulates OB differentiation and bone matrix mineralization, but lower concentrations of SP blocks osteogenic differentiation and induces proliferation of rat bone marrow MSCs and general protein synthesis . Recent studies showed that SP (10 −5 mM) increased ALP and osteocalcin activity in human OB proliferation and mineralization through increased GJIC between OBs . GJIC has important roles in conveying the anabolic effects of hormones and growth factors and regulating transcription of osteogenic markers…”
Section: Peptides From Nervous Systemsupporting
confidence: 86%
“…This effect was mediated by cyclic AMP and VPAC2 receptor. At 3 × 10 −5 mM, VIP enhanced human OB proliferation and mineralization through increased gap junction intercellular communication (GJIC) between OBs, an effect that was greater than that seen with substance P …”
Section: Peptides From Nervous Systemmentioning
confidence: 76%
See 2 more Smart Citations
“…This response pattern is suggestive for a higher rate of bone turnover and lower bone healing capacities as a consequence of early life stress, suggesting a concurrent joint downregulation, reduced bone remodeling and long-term destabilization. The neurotrophin NGF is important for the expression of cholinergic and sensory neuronal factors and hence for the development and the repair of bone, as demonstrated by reduced bone length when absent[14][15][16][17][18][19][20][21][22][23][24][25][26].The neuropeptide NPY promotes osteoblast differentiation and balances the effects of stress-induced bone-loss through beta-adrenergic stimulation, both with consequences for bone remodeling during healing[10,53,[56][57][58][59][60][61][62][63]. The neuropeptide VIPR1, finally, promotes bone mineralization[64][65][66][67][68] while TACR1 regulates osteoblasts, osteoclasts and mesenchymal stem cell functionality associated with protection from osteoporosis [2, 62, 69-85].…”
mentioning
confidence: 99%